Unwritten Writing: Deconstruction and the Folklore of Dice Games. - Kingston, Andrew (Comparatist, 2023)
The article focuses on the theme of ambivalence in historical dice games and their connection to writing and language. It explores the challenges of analyzing these games due to their unwritten nature, drawing on the term "epigrammatological" to describe its approach. Topics include the ambiguity associated with dice games, the intersection of ludic and linguistic ambivalence, and Plato's cautionary perspective on writing as a "pharmakon" with potential risks.